Next Generation Biofilm Inhibitors for Pseudomonas aeruginosa: Synthesis and Rational Design Approaches - S. Majik, Mahesh; T. Parvatkar, Prakash (Current Topics in Medicinal Chemistry, 2014)
The bacterial biofilms and the emergence of multiple drug resistance have become a major threat for current medical treatment of nosocomial infections. It has been estimated that about 65-80% of microbial infections in the developed countries are associated with biofilms. Given the prominence of biofilms in infectious diseases, increasing efforts toward the development of small molecules that will modulate bacterial biofilm development and maintenance is on the rise. Till date, marine natural products have shown a tremendous potential as pharma leads and also given new skeletons which would be used as biofilm/QS inhibitors. Medically relevant biofilm forming bacteria such as Pseudomonas aeruginosa which is most frequently isolated bacteria in nosocomial infection is believed to be a model organism for biofilm studies. Hence, in this review, we have highlighted the development of small molecules that inhibit and/or disperse bacterial biofilms of P. aeruginosa in particular. Additionally, the rational design approaches as well as synthetic methodologies along with biological studies has been accounted in this article.
Keywords: quorum sensing inhibitors